The handbook of development communication and social change - Wilkins, Karin Gwinn, 1962-; Tufte, Thomas; Obregon, Rafael (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
"This valuable resource offers a wealth of practical and conceptual guidance to all those engaged in struggles for social justice around the world. It explains in accessible language and painstaking detail how to deploy and to understand the tools of media and communication in advancing the goals of social, cultural, and political change"--Provided by publisher.
Part I. Communicating development and social change -- Part II. Developing strategic communication for social change -- Part III. Activist approaches for development and social change.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed February 7, 2014).
Keywords: Mass media -- Social aspects; Mass media -- Social aspects; Electronic books